Ripple effects of supervisor counterproductive work behavior directed at the organization: using affective events theory to predict subordinates' decisions to enact CWB. Issue 5 (19th October 2020) - Reynolds Kueny, Clair A.; Francka, Ellen; Shoss, Mindy K.; Headrick, Lucille; Erb, Kaitlyn
ABSTRACT: Exposure to others' counterproductive work behaviors may significantly impact employees at work. However, research has yet to thoroughly examine third-party reactions to CWB, particularly supervisor CWB. We build on affective events theory, research regarding supervisors' role in shaping work experiences, and research on vicarious effects of CWB to better understand how exposure to supervisor CWB-O can influence subordinates. Based on insights from preliminary studies, the within-person vignette-based focal study ( N = 1232 ratings nested in 176 raters) assessed when and how supervisor CWB-O predicts subordinates' decisions to enact their own CWB. Results suggest that supervisor CWB-O enacted in the context of a negative supervisor-subordinate relationship as well as severe, frequent supervisor CWB-O elicits negative subordinate reactions leading to greater intentions to enact CWB themselves.